The effectiveness of weekly versus daily Iron supplementation among Mild anemic pregnant women - Hashim, Haniza (2012)
THE EFFECTIVENESS OF WEEKLY VERSUS DAILY IRON SUPPLEMENTATION AMONG MILD ANEMIC PREGNANT WOMEN. Anemia is a public health problem that affects rich and poor population. Pregnant women are particularly vulnerable. Supplementation of diet with iron compounds during pregnancy has been recommended by international and local organizations for women of reproductive age. Traditionally, women have been prescribed iron supplement during pregnancy as daily regime. Recently, weekly supplementation has been suggested, since it takes advantage of the turnover time of intestinal mucosa cells favoring iron absorption regulation and is more economical and safer from the public health perspective.To study the effectiveness of weekly compared with daily iron supplementation among mild anemic pregnant women. This is a randomized controlled trial comparing the effectiveness of a weekly versus daily iron supplementation. Pregnant women at 12-20 weeks of gestation with hemoglobin of 9-llgm/dl were enrolled in the study. Total of 70 women were randomly allocated to receive 200mg oral dose of ferrous fumarate daily and 400mg of ferrous fumarate weekly. Hemoglobin and ferritin level were estimated at baseline and after 8 weeks of iron supplementation. Analysis of covariance (ANCOVA) was performed to compare the mean hemoglobin and ferritin level between the two groups at the end of study using baseline haemoglobin, ferritin, age, race, parity, period of gestation, income, and education as co-variates. A total of seventy mildly anemic women were recruited. Thirty five were assigned to daily group and another thirty five women were assigned to weekly group. There were no significant different in demographic and laboratory characteristic between the groups at the beginning of study. At the end of eight weeks supplementation there was no significant difference in the hemoglobin and ferritin values between the two groups. The supplementation of mild anemic pregnant women with 200 mg ferrous fumarate daily was as effective as weekly iron supplementation of 400 mg ferrous fumarate in terms of hemoglobin and ferritin response under conditions resembling the routine antenatal care.